2021
DOI: 10.1186/s13073-021-00866-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and non-genetic factors affecting the expression of COVID-19-relevant genes in the large airway epithelium

Abstract: Background The large airway epithelial barrier provides one of the first lines of defense against respiratory viruses, including SARS-CoV-2 that causes COVID-19. Substantial inter-individual variability in individual disease courses is hypothesized to be partially mediated by the differential regulation of the genes that interact with the SARS-CoV-2 virus or are involved in the subsequent host response. Here, we comprehensively investigated non-genetic and genetic factors influencing COVID-19-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…While awaiting data release via dbGaP, investigators may contact the senior author (Wenzel) of this study or go to the SARP website ( 46 ) to access to the data via the ancillary study mechanism for SARP. Count data for the SARP cohort was obtained from Stephanie Christianson (UCSF) and as published recently ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
“…While awaiting data release via dbGaP, investigators may contact the senior author (Wenzel) of this study or go to the SARP website ( 46 ) to access to the data via the ancillary study mechanism for SARP. Count data for the SARP cohort was obtained from Stephanie Christianson (UCSF) and as published recently ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the expression of ACE2, a tissue-protective mediator during lung damage, was found to be associated with interferon signaling in airway epithelial cells, and SARS-CoV-2 could exploit interferon-mediated stimulation of ACE2 to augment infection ( Ziegler et al, 2020 ). The differential expression of genes that are necessary for SARS-CoV-2 interaction and subsequent host response determine susceptibility to COVID-19, disease progression, and recovery ( Kasela et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNA sequencing of COVID-19 infected bronchial epithelial cells and bronchioalveolar immune cells revealed important cellular and molecular processes implicated in COVID-19 infection at the single-cell level and provided information about the mechanisms of disease severity ( Liu T. et al, 2020 ; Liao et al, 2020 ; Zhou et al, 2020 ). Notably, IL-17-associated signaling was significantly increased but not Th2-related inflammation following COVID-19 infection ( Kasela et al, 2021 ) . A recent study showed that SARS-CoV-2 infection caused a twofold higher induction of interferon stimulation compared to SARS-CoV in Calu-3 human epithelial cells and subsequent induction of cytokines such as IL6 or IL-10 ( Wyler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the influence of diet on ACE2 mRNA expression is based on interventions by dietary restrictions or weight loss [53] , [54] . Also, research related to ACE2 mRNA expression in organs, such as the heart or liver, is obtained from biopsies [55] , [56] . These facts reinforce the importance of an animal model for in vivo and ex vivo COVID-19 studies.…”
Section: Resultsmentioning
confidence: 99%